New method for rapid and dynamic quantification of elastase activity on sputum neutrophils from patients with cystic fibrosis using flow cytometry. Issue 4 (29th April 2020) - Hagner, Matthias; Frey, Dario L.; Guerra, Matteo; Dittrich, A. Susanne; Halls, Victoria S.; Wege, Sabine; Herth, Felix J.F.; Schultz, Carsten; Mall, Marcus A.
Small molecule FRET flow cytometry is a new method that enables rapid and sensitive quantification of surface-bound elastase activity on sputum neutrophils from patients with cystic fibrosis and potentially other neutrophilic airway diseases http://bit.ly/2IegeSB